$f$ is defined as
$$
f(x)=\sum_{k=1}^\infty\frac{\arctan(kx)}{k^2}\tag1
$$
For $x\le1$, the Mean Value Theorem says that there is a $h\in(0,x)$ so that
$$
\begin{align}
\frac{f(x)-f(0)}x
&=f'(h)\tag{2a}\\
&=\sum_{k=1}^\infty\frac1{k\left(1+k^2h^2\right)}\tag{2b}\\
&\ge\sum_{k=1}^{\lfloor1/h\rfloor}\frac1{2k}\tag{2c}\\
&\ge\frac12\log\left(\lfloor1/h\rfloor\right)\tag{2d}\\
&\ge\frac12\log\left(\lfloor1/x\rfloor\right)\tag{2e}
\end{align}
$$
This means that
$$
\begin{align}
f'(0)
&=\lim_{x\to0}\frac{f(x)-f(0)}x\tag{3a}\\
$$
f(x)=\sum_{k=1}^\infty\frac{\arctan(kx)}{k^2}\tag1
$$
For $x\le1$, the Mean Value Theorem says that there is a $h\in(0,x)$ so that
$$
\begin{align}
\frac{f(x)-f(0)}x
&=f'(h)\tag{2a}\\
&=\sum_{k=1}^\infty\frac1{k\left(1+k^2h^2\right)}\tag{2b}\\
&\ge\sum_{k=1}^{\lfloor1/h\rfloor}\frac1{2k}\tag{2c}\\
&\ge\frac12\log\left(\lfloor1/h\rfloor\right)\tag{2d}\\
&\ge\frac12\log\left(\lfloor1/x\rfloor\right)\tag{2e}
\end{align}
$$
This means that
$$
\begin{align}
f'(0)
&=\lim_{x\to0}\frac{f(x)-f(0)}x\tag{3a}\\